Manual of functions and competency-based management models under ISO 9001:2015 standards, textile sector (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2026)
In the current organizational context, competency-based management and the implementation of international quality standards have become fundamental pillars for ensuring business efficiency and competitiveness. Therefore, this article analyzed the level of awareness among companies regarding job manuals and competency-based models under the ISO 9001:2015 standard in textile factories in the parish of Pelileo. The objective of the research was to explore the current state of companies' awareness and implementation of quality management manuals. A quantitative approach was applied, with a descriptive-correlational scope and a non-experimental, cross-sectional design, using the survey technique and two questionnaires as instruments: one addressed to 103 factories in the parish of Pelileo and the other to 22 employees at the study factory. The results showed that 68.9% of factories were familiar with ISO 9001:2015 job manuals, and 56.3% of managers were favorable toward their implementation. A moderate positive correlation (Spearman's rho = 0.678; p < 0.001) was also found between job manuals and the implementation of the competency-based management model. In conclusion, competency-based job manuals aligned with ISO 9001:2015 standards improve clarity of responsibilities and reduce duplication of tasks, boosting productivity and competitiveness in the textile sector.
Keywords: quality management; ISO 9001:2015 standards; job descriptions; textile sector